Data for "Tensorial properties via the neuroevolution potential framework: Fast simulation of infrared and Raman spectra" - Xu, Nan; Rosander, Petter; Schäfer, Christian; Lindgren, Eric; Österbacka, Nicklas; Fang, Mandi; Chen, Wei; He, Yi; Fan, Zheyong; Erhart, Paul (Chalmers University of Technology, 2023)
This record contains neuroevolution potential (NEP) and tensor neuroevolution potential (TNEP) models (nep*.txt) for molecular water species, liquid water as well as barium zirconate, along with training data (*.zip). The models were constructed using GPUMD 3.9 (https://gpumd.org/).
Keywords: Neuroevolution potential; Machine-learned interatomic potential; Tensorial properties; Raman spectroscopy; Infrared spectroscopy; Physical Sciences; Fysik